Meta‐analysis of an artery‐first approach versus standard pancreatoduodenectomy on perioperative outcomes and survival. (13th April 2018) - Ironside, N.; Barreto, S. G.; Loveday, B.; Shrikhande, S. V.; Windsor, J. A.; Pandanaboyana, S.
Abstract : Background: The aim of this systematic review and meta‐analysis was to evaluate perioperative outcomes and survival in patients undergoing an artery‐first approach to pancreatoduodenectomy in comparison with those having standard pancreatoduodenectomy. Methods: A systematic search of PubMed, MEDLINE, Embase and the Cochrane Database of Systematic Reviews was performed in accordance with PRISMA guidelines. Comparative studies including patients who underwent artery‐first pancreatoduodenectomy and standard pancreatoduodenectomy were analysed. Results: Seventeen studies were included in the final analysis. There were 16 retrospective cohort or case–control studies and one RCT. A total of 1472 patients were included in the meta‐analysis, of whom 771 underwent artery‐first pancreatoduodenectomy and 701 had standard pancreatoduodenectomy. Intraoperative blood loss (mean difference –389 ml; P  < 0·001) and the proportion of patients requiring intraoperative transfusion (10·6 per cent (54 of 508) versus 40·1 per cent (186 of 464); P  < 0·001) were significantly lower in the artery‐first group. Although rates of perioperative mortality were comparable between the two groups, perioperative morbidity (35·5 per cent (263 of 741) versus 44·3 per cent (277 of 625); P = 0·002), and the incidence of grade B/C pancreatic fistula (7·4 per cent (26 of 353) versus 12·8 per cent (42 of 327); P = 0·031) were significantly lower in the artery‐first group. The R0 resection rate (75·8 per cent (269 of 355) versus 67·0 per cent (280 of 418); P  < 0·001) and overall survival (hazard ratio 0·72, 95 per cent c.i. 0·60 to 0·87; P  < 0·001) were significantly higher in the artery‐first group. Conclusion: The artery‐first approach to pancreatoduodenectomy may be associated with improved perioperative outcomes and survival. Abstract : Benefits to artery‐first approach